2021
DOI: 10.48550/arxiv.2110.06990
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scaling Laws for the Few-Shot Adaptation of Pre-trained Image Classifiers

Abstract: Empirical science of neural scaling laws is a rapidly growing area of significant importance to the future of machine learning, particularly in the light of recent breakthroughs achieved by large-scale pre-trained models such as GPT-3, CLIP and DALL-e. Accurately predicting the neural network performance with increasing resources such as data, compute and model size provides a more comprehensive evaluation of different approaches across multiple scales, as opposed to traditional point-wise comparisons of fixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Subsequent work has shown that similar scaling laws exist in generative models for other modalities (e.g., images, video, math, etc.) [35], audition [21], transfer from text to programming [36], few-shot adaptation of vision models [54], and more.…”
Section: Smooth General Capability Scalingmentioning
confidence: 99%
“…Subsequent work has shown that similar scaling laws exist in generative models for other modalities (e.g., images, video, math, etc.) [35], audition [21], transfer from text to programming [36], few-shot adaptation of vision models [54], and more.…”
Section: Smooth General Capability Scalingmentioning
confidence: 99%
“…This view might be summarized as the hope that defining features of biological intelligence will be inevitably unlocked by learning network architectures with the right connectional parameters at a sufficient scale of compute (i.e., proportional to input, model, and training sizes) to be attained in the future. Despite increasingly impressive capabilities, the latest and largest models, like GPT-3, OPT-175, DALL-E 2, and a recent "generalist" model called Gato [1][2][3][4][5][6], continue a long history of moving the goalposts for these biological features [7][8][9][10][11], which include abstraction and generalization; systematic compositionality of semantic relations; continual learning and causal inference; as well as the persistent ordersof-magnitude performance gaps reflected by low samplecomplexity and high energy-efficiency. Instead of presuming that scaling beyond trillion parameter models will yield intelligent machines from data soup, we infer that understanding biological intelligence sufficiently to formalize its defining features likely depends on characterizing fundamental mechanisms of brain computation and, importantly, solving how animals use their brains to construct subjective meaning from information [12][13][14][15][16][17][18][19].…”
Section: Mainmentioning
confidence: 99%